EFFECT OF ENVIRONMENTS AND TIMING ON GRAFTING SUCCESS IN KIWI FRUIT - LAL, H.; SINGH, V.P.; RAMAN, JAYANT (Annals of Agricultural Research, 2014)
An experiment on Kiwi fruit grafting technique was undertaken to find out the optimum time and environmental conditions for maximum grafting success and satisfactory growth of prepared grafted plants. Tounge grafting was performed at 15 days interval starting from 30th December, 2004 to 15th February, 2005 under two environments viz., open field and controlled polyhouse under Chaubattia climatic conditions. The maximum grafting success 66.0 percent and survival of grafts 87.2 percent were observed under polyhouse on 30th January, 2005. The success was 33.4 percent more under polyhouse than the open field condition. Date of grafting and environment had significant effect on shoot growth. The shoot growth and number of leaf size were 31.3 cm, 10.0 and 5.6cm more, respectively, under polyhouse as compared to open field.